If the value of x, $x = 2 + {2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}$, then the value of ${x^3} - 6{x^2} + 6x$ is
(a) 3
(b) 2
(c) 1
(d) None of these
Answer
Verified
509.4k+ views
Hint – In this question the value of x is given and we need to find the value of the given expression, take 2 on the left hand side towards x and take cube both the sides. Use the algebraic identity of ${\left( {a - b} \right)^3}$and others to reach the answer.
Complete step-by-step answer:
Given equation is
$x = 2 + {2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}$
So, we have to find out the value of ${x^3} - 6{x^2} + 6x$.
Now in given equation take 2 to L.H.S and take cube on both sides we have,
$ \Rightarrow x - 2 = {2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}$ ………………….. (1)
\[ \Rightarrow {\left( {x - 2} \right)^3} = {\left( {{2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}} \right)^3}\]
Now as we know ${\left( {a - b} \right)^3} = {a^3} - {b^3} - 3{a^2}b + 3a{b^2}$ and ${\left( {a + b} \right)^3} = {a^3} + {b^3} + 3{a^2}b + 3a{b^2}$ so, apply this property in above equation we have,
\[ \Rightarrow {x^3} - {2^3} - 3\left( {{x^2}} \right)\left( 2 \right) + 3x\left( {{2^2}} \right) = {\left( {{2^{\dfrac{2}{3}}}} \right)^3} + {\left( {{2^{\dfrac{1}{3}}}} \right)^3} + 3{\left( {{2^{\dfrac{2}{3}}}} \right)^2}\left( {{2^{\dfrac{1}{3}}}} \right) + 3\left( {{2^{\dfrac{2}{3}}}} \right){\left( {{2^{\dfrac{1}{3}}}} \right)^2}\]
Now simplify the above equation we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = {2^2} + 2 + 3\left( {{2^{\dfrac{2}{3}}}} \right)\left( {{2^{\dfrac{1}{3}}}} \right)\left( {{2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}} \right)\]
Now from equation (1) we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = {2^2} + 2 + 3\left( {{2^{\dfrac{2}{3} + \dfrac{1}{3}}}} \right)\left( {x - 2} \right)\]
Now simplify the above equation we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = 6 + \left( {3 \times 2\left( {x - 2} \right)} \right)\]
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = 6 + 6x - 12 = 6x - 6\]
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 6x = - 6\]
\[ \Rightarrow {x^3} - 6{x^2} + 6x = 8 - 6 = 2\]
So the required value of ${x^3} - 6{x^2} + 6x$ is 2.
So, this is the required answer.
Note – Whenever we face such types of problems the key concept is simply not to substitute the value of x in the given expression but somehow to simply and to change the expression into a bigger expression containing sub expressions whose values are known to us. This concept will help you get on the right track to reach the answer.
Complete step-by-step answer:
Given equation is
$x = 2 + {2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}$
So, we have to find out the value of ${x^3} - 6{x^2} + 6x$.
Now in given equation take 2 to L.H.S and take cube on both sides we have,
$ \Rightarrow x - 2 = {2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}$ ………………….. (1)
\[ \Rightarrow {\left( {x - 2} \right)^3} = {\left( {{2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}} \right)^3}\]
Now as we know ${\left( {a - b} \right)^3} = {a^3} - {b^3} - 3{a^2}b + 3a{b^2}$ and ${\left( {a + b} \right)^3} = {a^3} + {b^3} + 3{a^2}b + 3a{b^2}$ so, apply this property in above equation we have,
\[ \Rightarrow {x^3} - {2^3} - 3\left( {{x^2}} \right)\left( 2 \right) + 3x\left( {{2^2}} \right) = {\left( {{2^{\dfrac{2}{3}}}} \right)^3} + {\left( {{2^{\dfrac{1}{3}}}} \right)^3} + 3{\left( {{2^{\dfrac{2}{3}}}} \right)^2}\left( {{2^{\dfrac{1}{3}}}} \right) + 3\left( {{2^{\dfrac{2}{3}}}} \right){\left( {{2^{\dfrac{1}{3}}}} \right)^2}\]
Now simplify the above equation we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = {2^2} + 2 + 3\left( {{2^{\dfrac{2}{3}}}} \right)\left( {{2^{\dfrac{1}{3}}}} \right)\left( {{2^{\dfrac{2}{3}}} + {2^{\dfrac{1}{3}}}} \right)\]
Now from equation (1) we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = {2^2} + 2 + 3\left( {{2^{\dfrac{2}{3} + \dfrac{1}{3}}}} \right)\left( {x - 2} \right)\]
Now simplify the above equation we have,
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = 6 + \left( {3 \times 2\left( {x - 2} \right)} \right)\]
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 12x = 6 + 6x - 12 = 6x - 6\]
\[ \Rightarrow {x^3} - 8 - 6{x^2} + 6x = - 6\]
\[ \Rightarrow {x^3} - 6{x^2} + 6x = 8 - 6 = 2\]
So the required value of ${x^3} - 6{x^2} + 6x$ is 2.
So, this is the required answer.
Note – Whenever we face such types of problems the key concept is simply not to substitute the value of x in the given expression but somehow to simply and to change the expression into a bigger expression containing sub expressions whose values are known to us. This concept will help you get on the right track to reach the answer.
Recently Updated Pages
You are awaiting your class 10th results Meanwhile class 7 english CBSE
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Full Form of IASDMIPSIFSIRSPOLICE class 7 social science CBSE
Collective noun a of sailors class 7 english CBSE
Convert 200 Million dollars in rupees class 7 maths CBSE
Fill in the blanks with appropriate modals a Drivers class 7 english CBSE
What are the controls affecting the climate of Ind class 7 social science CBSE
The southernmost point of the Indian mainland is known class 7 social studies CBSE